Sistem Pendukung Keputusan Rekomendasi Program Ekskul Disekolah Menegah Kejuruan dengan Metode AHP dan TOPSIS - Tanjung, Erti Belastari; Zufria, Ilka; Armansyah, Armansyah (TIN: Terapan Informatika Nusantara, 2024)
Extracurricular activities are vital for developing students' personalities, talents, and abilities beyond the standard curriculum. However, a lack of effective information dissemination about extracurricular activities poses a challenge. To address this issue, a decision support system using Analytic Hierarchy Process (AHP) and Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) methods is needed, along with increasing students' awareness of the importance of extracurricular activities. This research aims to recommend extracurricular programs to students in vocational high schools. Specific issues include developing a literature review, designing a user-friendly system, tools for web-based decision support system development, and implementing AHP and TOPSIS methods for extracurricular recommendation systems. The research will be conducted at SMK Muhammadiyah 9 Medan, focusing on 93 selected Class X students. Recommendation criteria will include intelligence level, interests, concentration, memory, commitment, willingness, creativity, health history, and parental consent, based on the results of students' psychological tests. The AHP method will be used for criteria weighting, and TOPSIS will rank recommended extracurricular programs based on priority values. The research aims to provide 9 recommended extracurricular programs tailored to students' interests and talents, enhance researchers' skills in implementing AHP and TOPSIS methods, improve extracurricular program management efficiency, and increase student satisfaction with extracurricular activities. The decision support system developed in this research will benefit researchers, school administrators, and students, improving program management and student participation in extracurricular activities.The implementation results of extracurricular recommendations using the AHP and TOPSIS methods achieved an accuracy of 74%. Changes in accuracy may be influenced by the criteria used and inputted, as well as the minimum extracurricular activities inputted by the user.